Analisis Konflik Tokoh Utama dalam Naskah Drama Lautan Bernyanyi Karya Putu Wijaya - Aisyah, Nisa; Almauludi, Muhammad Hafizh; Safitri, Lulu (Suara Bahasa, 2025)
This research aims to determine the conflict of the main characters in the drama Lautan Bernyanyi by Putu Wijaya. This research method uses a descriptive qualitative approach from a literature perspective with the object being the drama manuscript Lautan Bernyanyi by Putu Wijaya. The data collected in this research is in the form of books, journals and notes. Data collection was carried out using reading, note-taking and library techniques. This method is used to explain the conflict between the main characters in the drama Lautan Bernyanyi by Putu Wijay in order to gain new knowledge about how the conflict occurred. The results of this research show that there are several conflicts experienced by the main characters in the drama Lautan Bernyanyi by Putu Wijaya. The conflicts are in the form of internal and external conflicts. In external conflict there is social conflict and physical conflict. The internal conflicts contained in this drama script are: (1) distrust and; (2) regret. Meanwhile, the external conflicts that researchers found in this drama script are: (1) resistance and; (2) threats